Extreme Idiopathic gigantomastia - Benna, Mehdi; Naser, Radhi Ben; Fertani, Yasmine; Ayadi, Mohammed Ali; Bettaieb, Ilhem; Chargui, Riadh; Hechiche, Monia; Gammoudi, Amor; Rahal, Khaled (International Journal of Research in Medical Sciences, 2018)
Gigantomastia is a rare mastopathy of unknown cause. Due to mechanical and psychological complications related to excessive breast weights and volume, effective surgical treatment is required. Most cases of gigantomastia in the literature are associated with pregnancy or puberty and very rare cases of spontaneous gigantomastia have been reported We report a 38 years old woman with an idiopathic gigantomastia treated successfully with Thorek technique.